Peruvian adaptation of the Pediatric Symptoms Checklist as a screening tool for behavioral and emotional problems in children and adolescents. - Cortez-Vergara, Carla P. (2022)
Objective: Adaptation to Peruvian population of the Pediatric Symptoms Checklist (PSC-17), a questionnaire that assists in the identification of emotional and behavioral problems in children and adolescents between 6 to 17 years. Method: On the basis of the original texts of PSC-17 in English and Spanish and the Chilean version, a committee of five experts proceeded to the adaptation of the 17 items for parents and caregivers and for adolescents. Results: Some items were kept identical to one of the two revised Spanish versions; others remained similar to the Chilean version, and some had to be slightly modified to match Peruvian Spanish. Conclusions: The final Peruvian version of the PSC-17 would facilitate the detection of mental health problems in children and adolescents in our country, even though it is still necessary to subsequently carry out pertinent studies of its psychometric properties.